Analisis SWOT Pelayanan Diva Family Karaoke Salemba Jakarta untuk Meningkatkan Kepuasan dan Loyalitas Pelanggan - Syarif Fitri (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
In the midst of increasingly fierce business competition, the growth of the entertainment world, especially the world of family karaoke in recent years has increased in Indonesia. The concentration of this research was conducted at Salemba Karaoke Family Diva in Jakarta, where the problem was to increase customer satisfaction and loyalty with SWOT analysis in the service of Salemba Karaoke Family Diva in Jakarta. This study uses a qualitative research approach with qualitative descriptive method where data collection uses observation and interviews to 1 shop manager at Salemba Diva Family Karaoke branch, 1 Salemba branch Diva Family Karaoke staff, and 5 Salemba Diva family Karaoke customers. The results of this study that the Diva Family Management of the Salemba Karaoke Branch managed to find strength, power, opportunities and threats. And by reviewing this, Diva Karaoke, Salemba Branch can improve customer satisfaction and loyalty.